(untitled) (Journal of Science and Technology Research, 2024)
This research focuses on synthesizing and characterizing cobalt oxide (Co3O4) nanoparticles using an ionizing radiation technique. The precursor cobalt (III) hydroxide, Co(OH)3 was chemically synthesized from cobalt (II) nitrate hexahydrate, [Co(NO3)2·6H2O] as a solution precipitation technique in an alkali medium. The Co(OH)3 precursor was then exposed to a 60Co gamma radiation source at a dose of 30 kGy with a dose rate of 10 kGy/hr to obtain Co3O4 nanoparticles. The synthesized Co3O4 nanoparticles were subjected to various characterization techniques. Fourier-Transform Infrared (FT-IR) spectroscopic analysis of raw Co(NO3)2·6H2O, Co(OH)3 precursor, and Co3O4 nanoparticles revealed distinctive absorption peaks for the Co3O4 nanoparticles. X-ray diffraction analysis exhibited different characteristic diffraction angles (2θ) values, lattice spacing, and crystal size for the Co3O4 nanoparticles. SEM images of raw Co(NO3)2·6H2O, Co(OH)3 precursor, and Co3O4 nanoparticles displayed distinguishable surface morphologies. Additionally, the thermogravimetric analysis provided insight into the decomposition behaviour of the Co(OH)3 precursor. The characterization data indicated that the ionizing radiation-synthesized Co3O4 nanoparticles possessed similar properties to those synthesized using conventional methods. Furthermore, the ionizing radiationsynthesized Co3O4 nanoparticles demonstrated an efficient photo-catalytic effect in the degradation of methylene blue (MB) dye. Therefore, this study shows the successful synthesis and characterization of Co3O4 nanoparticles using an ionizing radiation technique, highlighting their potential application in photo-catalysis for the degradation of MB dye. J. of Sci. and Tech. Res. 6(1): 175-185, 2024